HuR stabilizes HTT mRNA via interacting with its exon 11 in a mutant HTT-dependent manner. Issue 4 (2nd April 2020) - Zhao, Quan; Li, Chen; Yu, Meng; Sun, Yimin; Wang, Jian; Ma, Lixiang; Sun, Xiaoli; Lu, Boxun
ABSTRACT: Huntington's Disease (HD) is a monogenetic neurodegenerative disorder mainly caused by the cytotoxicity of the mutant HTT protein (mHTT) encoded by the mutant HTT gene. Lowering HTT mRNA has been extensively studied as a potential therapeutic strategy, but how its level is regulated endogenously has been unclear. Here we report that the RNA-binding protein (RBP) HuR interacts with and stabilizes HTT mRNA in an mHTT-dependent manner. In HD cells but not wild-type cells, siRNA knockdown or CRISPR-induced heterozygous knockout of HuR decreased HTT mRNA stability. HuR interacted with HTT mRNA at a conserved site in exon 11 rather than the 3ʹ-UTR region of the mRNA. Interestingly, this interaction was dependent on the presence of mHTT, likely via the activation of MAPK11, which enhanced cytosolic localization of the HuR protein. Thus, mHTT, MAPK11 and HuR may form a positive feedback loop that stabilizes HTT mRNA and enhances mHTT accumulation, which may contribute to HD progression. Our data reveal a novel regulatory mechanism of HTT mRNA via non-canonical binding of HuR.